Epidemiology of Anterior Cruciate Ligament Injury in Italian First Division Soccer Players. (May 2020) - Grassi, Alberto; Macchiarola, Luca; Filippini, Matteo; Lucidi, Gian Andrea; Della Villa, Francesco; Zaffagnini, Stefano
Background: The burden of anterior cruciate ligament (ACL) injury in professional soccer players is particularly relevant as it represents a potentially career-threatening injury. Hypothesis: Our hypotheses were that (1) injury incidence rate would be similar to that reported in the literature, (2) we would identify a uniform distribution of the injuries along the season, and (3) injury incidence rate would be similar in high-ranked and lower ranked teams, based on final placement in the league. Study Design: Descriptive epidemiological study. Level of Evidence: Level 4. Methods: Professional male soccer players participating in the Serie A championship league in 7 consecutive seasons (2011-2012 to 2017-2018) were screened to identify ACL injuries through the online football archivetransfermarkt.com . Exposure in matches and training were calculated. Results: There were 84 ACL injuries found (mean player age, 25.3 ± 4.2 years). Overall, 25% of ACL injuries were reruptures (15%) or contralateral injuries (10%). ACL incidence rate was 0.4215 per 1000 hours of play during Serie A matches, 0.0305 per 1000 hours of training (rate ratio [RR], 13.8; 95% CI, 8.4-22.7; P < 0.0001), and 0.0618 per 1000 hours of total play. Injury distribution had a bimodal peak, with the highest number of events in October and March. Alternatively, training injuries peaked in June and July. A significantly higher incidence rate was found for the teams ranked from 1st to 4th place compared with those ranked 5th to 20th (0.1256 vs 0.0559 per 1000 hours of play; RR, 2.2; 95% CI, 1.4-3.6; P = 0.0003). A similar finding was found for injury incidence proportion (3.76% vs 1.64%; P = 0.0003). Conclusion: The overall incidence rate of ACL injuries in Italian Serie A was 0.062 per 1000 hours, with a 14-fold risk in matches compared with training. Relevantly, 25% were second injuries. Most injuries occurred in October and March, and an almost 2-fold incidence rate and incidence proportion were noted in those teams ranked in the first 4 positions of the championship league. Clinical Relevance: Knowing the precise epidemiology of ACL injury in one of the most competitive professional football championship leagues could help delineate fields of research aimed to investigate its risk factors.